A "Double-Hit" Translocation Sarcoma—First Report of the Co-occurrence of EWSR1-FLI1 and MTMR2-NTRK2 Fusion in a Small Round Blue Cell Sarcoma. Issue 2 (March 2020) - Vargas, Ana Cristina; Kurek, Caroline; Bonar, Fiona; Maclean, Fiona; Qiu, Min Ru; Boyle, Richard; Brookwell, Ross; Gill, Anthony J.
Abstract : Abstract: We report a case of a 51-year-old man with primary diagnosis of Ewing sarcoma confined to the soft tissue, associated with EWSR1-FLI1 gene fusion demonstrated by fluorescence in situ hybridization (FISH). Six years after the diagnosis, immunohistochemistry for NTRK (neurotrophic receptor tyrosine kinase 1–3) was performed on this tumor using 2 Pan-Trk rabbit monoclonal antibodies, A7H6R (Cell Signaling Technology, Danvers, Mass) and EPR17341 (Abcam, Cambridge, Mass). Both clones showed diffuse moderate to strong cytoplasmic expression including presence of nuclear stain. RNA sequencing demonstrated the co-occurrence of MTMR2-NTRK2, a novel gene fusion, in the same tumor block used for EWSR1 FISH testing. While FISH for NRK2 did not confirm gene rearrangement, an atypical signal pattern was identified. This case challenges the concept that NTRK fusions are mutually exclusive with other oncogenic drivers. The clinical course of this patient has also been unusual as the tumor has followed an indolent course with no evidence of recurrent or metastatic disease.